Toward a Richer Understanding of Country of Origin - Gregg, John Robert (Curtin University, 2016)
In this dissertation we develop an alternative theoretical framework to better understand the meaning of Country of Origin effects. We utilise the two-component view of attitudes, which posits attitudes are formed through the combined influence of cognitions and affect toward the attitude object. We develop hypotheses to investigate how these dimensions influence attitudes towards countries and their products. Empirical verification provides support for the use of the two component view of attitudes in Country of Origin research.